Potent Inhibition of Zika Virus Replication by Aurintricarboxylic Acid - Park, Jun-Gyu; Ávila-Pérez, Ginés; Madere, Ferralita; Hilimire, Thomas A.; Nogales, Aitor; Almazán, Fernando; Martínez-Sobrido, Luis (Frontiers in Microbiology, 2019)
Zika virus (ZIKV) is one of the recently emerging vector-borne viruses in humans and is responsible for severe congenital abnormalities such as microcephaly in the Western Hemisphere. Currently, only a few vaccine candidates and therapeutic drugs are being developed for the treatment of ZIKV infections, and as of yet none are commercially available. The polyanionic aromatic compound aurintricarboxylic acid (ATA) has been shown to have a broad-spectrum antimicrobial and antiviral activity. In this study, we evaluated ATA as a potential antiviral drug against ZIKV replication. The antiviral activity of ATA against ZIKV replication in vitro showed median inhibitory concentrations (IC50) of 13.87 ± 1.09 µM and 33.33 ± 1.13 µM in Vero and A549 cells, respectively; without showing any cytotoxic effect in both cell lines (median cytotoxic concentration (CC50) > 1,000 µM). Moreover, ATA protected both cell types from ZIKV-induced cytopathic effect (CPE) and apoptosis in a time- and concentration-dependent manner. In addition, pre-treatment of Vero cells with ATA for up to 72 hours also resulted in effective suppression of ZIKV replication with similar IC50. Importantly, the inhibitory effect of ATA on ZIKV infection was effective against strains of the African and Asian/American lineages, indicating that this inhibitory effect was not strain dependent. Overall, these results demonstrate that ATA has potent inhibitory activity against ZIKV replication and may be considered as a potential anti-ZIKV therapy for future clinical evaluation.